G186(P) 'paediatric pitstop' general academic paediatric research workshop. (12th March 2018) - Purcell, C; Martins, C; Balfe, J; Molloy, EJ
Abstract : Aims: Research and audit activity is mandatory for Paediatric trainees with one annual audit the minimum expected standard. Senior support has been shown to be helpful in facilitating successful project completion. With this aim a General Paediatric research workshop was established, providing a supportive forum for discussion and advice on individual projects. This paper will describe the development and outomes of this project. Methods: An open, monthly, Consultant-supported, breakfast meeting was convened facilitating junior doctor attendance. Participants were allocated 5 min to provide a short focused presentation, noting progress and highlighting difficulties in research projects. Group input and structured feedback was encouraged to optimise ideas and solutions. Deadlines and targeted publications were advised with an aim to ensure project success. Attendances were recorded, weekly logs kept of each project with recommended advice and timelines for completion. Results: 11 workshops have been held to date; involving Consultants, junior hospital doctors, Nurse Specialists, Dieticians and Physiotherapists. 17 projects have been submitted as presentations for the upcoming Irish Paediatric Association (IPA) Conference. In addition a further 10 projects are due for presentation at a variety of European Meetings in 2017, 1 project is now informing National UTI Guidelines and 1 project has been submitted for publication at a peer-reviewed Journal. In the year prior to the Research workshop initiative; 2 oral presentations and 9 (P) presentations were accepted at the IPA Conference. The feedback to date is overwhelmingly positive with Junior Doctors reporting greater support, interest and involvement in research. Conclusions: The workshops continue and have expanded to include the General Paediatric Departments of Dublin's 2 other Children's Hospitals. The opening of Ireland's new National Paediatric Hospital in 2022 will provide great opportunities for further development of the Academic Department of General Paediatrics. The goal is that this initiative will contribute to a structured template for further Research workshops across all Paediatric centres in Ireland and provide a collaborative Network for General Paediatric Research in the future.